Dual inhibition of PI3K and mTOR in cancer therapy: Mechanisms, clinical potential, and future perspectives. - Al Anta, Tasneem; Al Shehadat, Ola; Taneera, Jalal; Aleidi, Shereen M.; Abuhelwa, Ahmad A.; Alzoubi, Karem H.; Semreen, Mohammad H.; El-Huneidi, Waseem; Abu-Gharbieh, Eman; Bustanji, Yasser (Pharmacy Practice (1886-3655))
The PI3K/AKT/mTOR signaling system is essential for controlling cell growth, survival, proliferation, and metabolism, rendering it a significant therapeutic target in cancer treatment. Dysregulation of this system is commonly reported in numerous cancers, facilitating tumor development and resistance to standard therapy. Dual inhibitors that concurrently target both Phosphatidylinositol 3-Kinase (PI3K) and Mammalian Target of Rapamycin (mTOR) provide a more thorough inhibition of this pathway, reducing the deficiencies of single-agent inhibitors and bypassing compensatory mechanisms that frequently result in therapeutic resistance. This review investigates the molecular basis of dual PI3K/mTOR inhibition, emphasizing its potential to improve cancer treatment effects. We provide a concise overview of the preclinical and clinical data that substantiates the efficacy of dual inhibitors in various malignancies, including breast, prostate, colorectal, pancreatic, ovarian, and lung cancers. Significant antitumor activity has been demonstrated by notable dual inhibitors when combined with chemotherapy or targeted agents. However, challenges such as resistance and toxicity persist. Additional research is required to refine dose protocols, optimize patient selection by biomarker identification, and investigate combination drugs to improve efficacy while reducing undesirable effects. The advancement of nanoformulations has demonstrated potential in enhancing medicine delivery and reducing systemic toxicity. Dual PI3K/mTOR inhibitors constitute a promising therapeutic strategy, providing significant enhancements in tailored cancer treatment, particularly for individuals with resistant or aggressive malignancies.